The misunderstood Jew : the Church and the scandal of the Jewish Jesus - Levine, Amy-Jill, 1956- (New York, Harper Collins Publishers, 2006)
"Mixing rigorous scholarship with helpings of both wit and pastoral care, Amy-Jill Levine reveals Jesus as The Misunderstood Jew. Levine shows how Christians often misunderstand Judaism in general, misunderstand the New Testament in particular, and thus yank Jesus out of his Jewish context?resulting in intolerance (and sometimes outright hatred) of Jews. She doesn't let Jews off the hook either, cutting through willful ignorance of Jesus and his message. A Jewish scholar who teaches in a primarily Protestant divinity school in Nashville, Tennessee?the buckle of the Bible Belt?Levine offers a unique, deeper understanding of who Jesus was and what he taught"--Publisher website (September 2007).
Jesus and Judaism -- From Jewish sect to gentile church -- The New Testament and anti-Judaism -- Stereotyping Judaism -- With friends like these ... -- Distinct canons, distinct practices -- Quo vadis?
Includes bibliographical references (pages 233-240) and indexes.
Keywords: Jesus Christ -- Jewishness; Bible. -- Criticism, interpretation, etc; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Jews in the New Testament; Judaism (Christian theology)